Evaluasi Standar Dan Kelayakan Mutu Bangunan Mako Polsek Dalam Rangka Pelayanan Prima Polri - Harvin Raslin (Jurnal Litbang Polri, 2022)
The background of this research is that there are several obstacles to the condition of the Polsek building in providing excellent service to the community and supporting the performance of the Police.In discussing it, it is carried out through qualitative and quantitative approaches as well as the evaluation theory approach and excellent service. The data collection process was carried out using the method of Focus Group Discussion (FGD ), filling out questionnaires, interviews and observations. The targeted respondents were members of the Police at the Polres and Polsek Levels. The research location as a sampling test consisted of 10 (ten) Polda and 1 (one) Polsek for each Polres. Meanwhile, the research object is in the form of structure and non-structure of the Polsek building (aspects of public and social facilities).The research was conducted from February 8 s / d March 11, 2021, involving Researcher Center for Police and partners as a consultant namely slog Police, University of Indonesia (UI), the Agency for the Assessment and Application of Technology (BPPT) and PT. Rekacipta Kreasindo. From the implementation of this research, several constraints have been found related to the structure and non-structure of the Mako Polsek building which are not in line with the standards and feasibility of building quality. And these constraints formulated several recommendations for improving the quality and standards of buildings. Based on the findings from the sampling test, it can be seen that the majority of Mako Polsek buildings visited do not meet the requirements for safe construction, especially those at Polsek that were built 15 years ago or earlier. Many of the old Polsek buildings also did not have certificates and IMBs. Public and social facilities are inadequate, but they can be improved, for example by paying more attention to facilities for residents with disabilities. Other things that need to be considered are the standardization of the installation of CCTV and internet networks, as well as adjustments to the harwat budget for routine maintenance of buildings.